A method for estimating special endurance in wrestlers - Shiyan, V. V. (International Journal of Wrestling Science, 2011)
An objective measure of a wrestler.s endurance level was developed through a highly regulated testing program of special physical loading and biochemical measures. A formula for the calculation of a wrestler.s special endurance coefficient (SEC) was developed. Wrestlers perform a body lock throw over the chest with a dummy that is 1/3 of their weight category to model the special workload of the sport. The special endurance test procedures consist of 3 parts . a special warm-up, rest and the test. Through test results pedagogical and biochemical indicators are measured which can characterize the efficiency of standard specific task. Guidelines for estimating a wrestler.s special endurance, and therefore their competition readiness are provided. These were developed from the results from many years of observation and testing of highly qualified wrestlers. Methods for the use of lactate measures, rather than pH, are also provided.